2006
DOI: 10.1002/bmc.672
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive multi‐dimensional liquid chromatographic separation in biomedical and pharmaceutical analysis: a review

Abstract: ‘Multi‐dimensional’ liquid separations have a history almost as long as chromatography. In multi‐dimensional chromatography the sample is subjected to more than one separation mechanism; each mechanism is considered an independent separation dimension. The separations can be carried out either offline via fraction collection, or directly coupled online. Early multi‐dimensional separations using combinations of paper chromatography, electrophoresis and gels, in both planar and columnar modes are reviewed. Devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(47 citation statements)
references
References 101 publications
0
47
0
Order By: Relevance
“…Because of the tremendously higher separation power of LC Â LC when compared with its 1D-LC counterpart, the technique has been employed in several fields, e.g., polymers, pharmaceuticals and biological mixtures, natural products, environmental and petrochemical samples, and has been the subject of various reviews (Liu and Lee, 2000;Evans and Jorgenson, 2004;Guttman et al, 2004;Stroink et al, 2005;Dixon et al, 2006;Jandera, , 2012Shalliker and Gray, 2006;Shellie and Haddad, 2006;Dugo et al, 2008a,b;Pol and Hyotylainen, 2008;François et al, 2009a;Herrero et al, 2009;Sandra et al, 2009;Berek, 2010;Pierce et al 2012;Sarrut et al, 2014).…”
Section: Chaptermentioning
confidence: 99%
“…Because of the tremendously higher separation power of LC Â LC when compared with its 1D-LC counterpart, the technique has been employed in several fields, e.g., polymers, pharmaceuticals and biological mixtures, natural products, environmental and petrochemical samples, and has been the subject of various reviews (Liu and Lee, 2000;Evans and Jorgenson, 2004;Guttman et al, 2004;Stroink et al, 2005;Dixon et al, 2006;Jandera, , 2012Shalliker and Gray, 2006;Shellie and Haddad, 2006;Dugo et al, 2008a,b;Pol and Hyotylainen, 2008;François et al, 2009a;Herrero et al, 2009;Sandra et al, 2009;Berek, 2010;Pierce et al 2012;Sarrut et al, 2014).…”
Section: Chaptermentioning
confidence: 99%
“…Two separation methods are orthogonal if the separation mechanisms involved are independent of each other and show distinct retention profiles or provide different selectivities [115]. However, many separation modes have retention mechanisms in common, making the realisation of perfect orthogonality in practice difficult [116,117]. In essence, the advantage of an LC×LC separation is not fully utilised if the entire 2-dimensional separation space is not completely utilised, and this require the combination of orthogonal separations.…”
Section: Equation 23mentioning
confidence: 99%
“…This increase is generally due to improved detection of lower abundance species, which are ultimately better resolved from species that are present either in higher abundance or have higher proton affinities or surface activities. A direct approach for increasing the separation peak capacity is through the inclusion of additional separation dimensions (reviewed in [110]), although the incorporation of multiple separation dimensions can result in increased analysis time and sample consumption. However, Stoll et al [111] recently reported the development of a high speed, comprehensive online 2D-LC-UV method based on the use of ultra-fast, high temperature gradient chromatography and the application of this method to the analysis of the low molecular weight components of maize seedlings.…”
Section: High-efficiency Lc Separationsmentioning
confidence: 99%